APHIDOCOLOUS ANTS OF THE GENUS POLYRHACHIS FR. SMITH FROM MANIPUR - DEVI, C. MANMOHIN; SINGH, T.K.; NILAMAN, L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Ten species of aphidocolous ants under the genus Polyrhachis Fr. Smith including five species as new records in respect to their aphidassociation from India are reported.